A Comprehensive Examination of the Impacts of the Circular Economy Within the ESG: Evaluating New Metrics and Interactions - Macher, Gergely Zoltán; Szigeti, Cecília (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper provides an examination of the impacts of the circular economy within the framework of ESG criteria, emphasizing the interplay between these domains. The research aims to explore how circular economy principles can enhance ESG performance while identifying synergies and trade-offs across the three pillars. A methodology leveraging European Union datasets and indicators is applied, comparing to the ESG performance values of individual European Union member states. The findings indicate that integrating circular economy practices into ESG strategies enhances environmental outcomes, such as resource efficiency and waste reduction, while fostering social equity and improving governance transparency. However, challenges related to metric standardization and data harmonization across regions present limitations. The paper provides implications for policymakers, businesses, and investors by offering a framework for embedding circular economy principles within ESG strategies to drive sustainable development. The novelty of the research lies in the use of the first coherent and comprehensive index database for comparisons, leveraging European Union data to deepen the understanding of the relationships between circular economy principles and ESG (environmental, social, and governance) domains. By addressing a gap in the literature, this work contributes to the development of actionable tools for assessing and improving sustainability practices across industries.